Saída das ruas ou reconstrução de vida: a trajetória de estudantes universitários ex-moradores de rua em São Paulo - Marcolino, Sheila Costa (2012)
The aim of this research is identifying in the trajectory of university students, who are also former homeless people in Sao Paulo, objective and subjective elements that contributed with their process of getting off the streets. The narrative of the researched subjects, besides presents a unique process that differentiates them in the context of the homelessness, conveys throughout their own voices and experiences an assessment of the social service which they accessed and used as homeless people. Thus, this study displaces the debate to the realm of effectiveness of the homeless people care policy, focusing on the social service s outcomes in the subjects process of overcoming and getting off the streets. The acknowledgment of social movements, the production of knowledge on homelessness, and the construction of homeless people care policy in Sao Paulo in the last 10 years, are fundamentally important for this research. This is because the achievements, stagnations and retrocession which historically have shaped the construction of that policy point out two premises: the first has an emergency character with a pattern focus based on job placement as the way to get people off the streets, and the second integrates principles of dignity, citizenship and recognition of the subject as well as the variety of needs and human capacity and potential. This latter approach suggests a broader process and articulations leading to the subjects autonomy for reconstruction of their lives